Casos y cosas: semanario popular (Vol. 2, No. 54) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Correo de brujas, Y las cadenas...?, El amor es así...., Las solteras y el aeroplano, ¿Quiere ud. besar?, Correo franco y con...tranqueza

ENGLISH: Witches' mail, And the chains..., Love is like this ...., The bachelorettes and the airplane, Do you want to kiss, Frank mail and with...peace of mind
Cases and things: popular weekly (Vol. 2, No. 54)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas